2014
DOI: 10.1038/nutd.2014.27
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiponectin levels and risk of type 2 diabetes in the Japanese

Abstract: Background:Adiponectin has anti-inflammatory and insulin-sensitizing properties. Prospective studies have consistently shown a lower risk of type 2 diabetes among those with higher circulating adiponectin levels.Objective:We examined prospectively the association between serum adiponectin levels and type 2 diabetes risk among Japanese workers, taking visceral fat mass into account.Subjects and methods:Subjects were 4591 Japanese employees who attended a comprehensive health screening in 2008; had biochemical d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…Furthermore, for HOMA-IR ratio group (Figure 4), WMD in adiponectin showed a trend of a direct correlation except HOMA-IR ratio <1. 36. Additionally, WMDs in adiponectin showed a trend of direct correlation in subgroups of BMI and age ( Figures 5 and 6).…”
Section: Subgroup Analysismentioning
confidence: 80%
See 1 more Smart Citation
“…Furthermore, for HOMA-IR ratio group (Figure 4), WMD in adiponectin showed a trend of a direct correlation except HOMA-IR ratio <1. 36. Additionally, WMDs in adiponectin showed a trend of direct correlation in subgroups of BMI and age ( Figures 5 and 6).…”
Section: Subgroup Analysismentioning
confidence: 80%
“…A cross-sectional, genetic epidemiology study in 2009 with 1,599 American Samoan adults suggested that adiponectin is an independent risk factor of type 2 diabetes, and might help distinguish those at higher risk of developing this disease 35 . Furthermore, a most recent and up-to-date cohort study in 2014 carried out by Yamamoto Sin Japan suggested that higher levels of circulating adiponectin are associated with a lower risk of type 2 diabetes, and that adiponectin could confer a benefit in both persons with and without prediabetes 36 . The same results were shown in other studies [37][38][39] .…”
Section: Discussionmentioning
confidence: 99%
“…No significant interaction between BMI and adiponectin in association with risk of developing GDM was found in a nested case-control study among US pregnant women [20]. Similarly, non-significant interactions of adiposity measures and adiponectin levels in relation to T2DM risk were observed in some [54], although not all [55], studies conducted in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced adiponectin expression correlates with insulin resistance in mouse models, whereas mice with adiponectin ablation exhibit moderate insulin resistance and glucose intolerance, implying a protective effect of adiponectin against insulin resistance. In the clinical setting, reduced adiponectin levels have been reported in obese and T2DM patients, whereas higher adiponectin levels are associated with a lower risk of T2DM across diverse populations . Mechanistic studies have also revealed that adiponectin alleviates insulin resistance via reducing triglyceride content in muscle and liver in obese mice, while promoting adipocyte proliferation and differentiation as well as enhancing insulin responsiveness …”
Section: Antidiabetic Potential Of Fgf21mentioning
confidence: 99%